FINDINGS OF EVALUATION IN PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2012)
The objective is to diagnose the issue as assessment is understood by teachers of physical education. We tried toascertain what understanding of the topic, its importance, ways to assess aspects evaluated and its reflection in the teachinglearningprocess. It is understood that the assessment is a mandatory and permanent teaching job to do in teaching, followingstep by step the process of teaching and learning. From this, the assessment should be compared with the proposed objectives,evaluating their progress, difficulties, turning them as needed.The research is descriptive and was conducted with 20 physicaleducation teachers working in schools of St. Andrew, through a questionnaire. The results made it possible to see that you canuse that practice teaching as a way to enhance the student's progress and reassess its applicability, guiding new planning.Among the teachers surveyed, it was found that 100% of them evaluate the physical education classes, 50% performassessment to verify student learning, 37.5% perform diagnostic evaluation, 33% performed the evaluation at each stage oflearning , and most of them evaluates all aspects of human behavior. The evaluation and is a complex issue has great relevancein education that require evaluators and evaluated their understanding of the true meaning in the learning process. It wasconcluded that teachers use multiple forms of assessment instruments and to understand how students develop. The data showthat many teachers assess their students during classes, from the implementation of proposed activities, noting the evolution oflearning in everyday life at school. However, consider various aspects in their evaluation as the social, emotional, cognitive, andmotor, which in turn leads to the possibility of working during the school year with various forms of assessment.
Keywords: physical education; assessment; methodology.